LivHeart: A Multi Organ‐on‐Chip Platform to Study Off‐Target Cardiotoxicity of Drugs Upon Liver Metabolism. Issue 8 (29th January 2023) - Ferrari, Erika; Visone, Roberta; Monti, Elisa; Torretta, Enrica; Moretti, Matteo; Occhetta, Paola; Rasponi, Marco
Abstract: The drug discovery and development process is still long, costly, and highly risky. The principal attrition factor is undetected toxicity, with hepatic and cardiac toxicities playing a critical role and being the main responsible of safety‐related drug withdrawals from the market. Multi Organs‐on‐Chip (MOoC) represent a disruptive solution to study drug‐related effects on several organs simultaneously and to efficiently predict drug toxicity in preclinical trials. Specifically focusing on drug safety, different technological features are applied here to develop versatile MOoC platforms encompassing two culture chambers for generating and controlling the type of communication between a metabolically competent liver model and a functional 3D heart model. The administration of the drug Terfenadine, a cardiotoxic compound liver‐metabolized into the noncardiotoxic Fexofenadine, proves that liver metabolism and a fine control over drug diffusion are fundamental to elicit a physio‐pathological cardiac response. From these results, an optimized LivHeart platform is developed to house a liver model and a cardiac construct that can be mechanically trained to achieve a beating microtissue, whose electrophysiology can be directly recorded in vitro. The platform is proved able to predict off‐target cardiotoxicity of Terfenadine after liver metabolism both in terms of cell viability and functionality. Abstract : The LivHeart Multi Organs‐on‐Chip platform encompasses a metabolically competent liver model and a functional 3D heart model for safety screening of compounds. Different technological features are applied to finely control the communication between the hepatic and the cardiac culture chambers. The platform is able to predict off‐target cardiotoxicity after liver metabolism, as here demonstrated with Terfenadine.